Notes on TQFT Wire Models and Coherence Equations for SU(3) Triangular Cells - Coquereaux, R.; Isasi, E.; Schieber, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
After a summary of the TQFT wire model formalism we bridge the gap from Kuperberg equations for SU(3) spiders to Ocneanu coherence equations for systems of triangular cells on fusion graphs that describe modules associated with the fusion category of SU(3) at level k. We show how to solve these equations in a number of examples.